2023
DOI: 10.1097/hep.0000000000000694
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of AGILE 3+ score for advanced fibrosis in patients with NAFLD: A systematic review and meta-analysis

Andrea Dalbeni,
Rosa Lombardi,
Matteus Henrique
et al.

Abstract: Background and Aims: A simple non-invasive score, the Agile3+ score, combining liver stiffness measurement (LSM), aspartate aminotransferase/alanine aminotransferase ratio, platelet count, diabetes status, sex, and age, has been proposed for identification of advanced fibrosis in patients with suspected non-alcoholic fatty liver disease (NAFLD). We performed a systematic review and meta-analysis of observational studies to evaluate the diagnostic accuracy of the Agile 3+ score in identifying patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The time a patient has their baseline LSM might depend on the aetiology of disease and other parameters and should be taken into consideration when interpreting the results. Unfortunately, we lacked laboratory data for a majority of the cohort, thus being unable to compare the prognostic ability of LSM in combination with lab parameters such as Agile 3+, 39 or with the prognostic ability of other non-invasive biomarkers such as FIB-4. Since this was a register-based study, clinical parameters that can be important risk factors of progression of chronic liver disease, such as alcohol consumption or BMI, were also lacking.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The time a patient has their baseline LSM might depend on the aetiology of disease and other parameters and should be taken into consideration when interpreting the results. Unfortunately, we lacked laboratory data for a majority of the cohort, thus being unable to compare the prognostic ability of LSM in combination with lab parameters such as Agile 3+, 39 or with the prognostic ability of other non-invasive biomarkers such as FIB-4. Since this was a register-based study, clinical parameters that can be important risk factors of progression of chronic liver disease, such as alcohol consumption or BMI, were also lacking.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Nonalcoholic fatty liver disease (NAFLD), as a globally prevalent metabolic-related disease of the liver, affects approximately 38% of the world’s population, and as such, it significantly threatens public health ( 1 ). Most patients with NAFLD do not experience discomfort, whereas a small percentage may present with fatigue, epigastric discomfort, or vague pain ( 2 ). While its typical characteristic include excessive lipid accumulation in the liver without alcohol abuse, some NAFLD patients can further progress to nonalcoholic steatohepatitis, liver fibrosis, cirrhosis, and eventually hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, meta-regression analyses on Agile3þ scores revealed that the diagnostic accuracy was partly mediated by age, body mass index, and sex, although sex did not reach statistical significance (p = 0.06). 4 The diagnostic performance of Agile scores in their Brazilian cohort appears to be poor, but they did not examine whether the clinical backgrounds affected their diagnostic performance, and this issue remains unclear. These factors could be identified and discussed in their future analyses.…”
mentioning
confidence: 99%